PENERAPAN PENDEKATAN PROSES UNTUK MENINGKATKAN KETERAMPILAN MENULIS NARASI SISWA KELAS III SEKOLAH DASAR - Jamaludin Jamaludin; Siti Halidjah; Suparjan Suparjan (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2021)
AbstractThis study aims to elucidate the application of a process approach that can improve the narrative writing skills of grade III of students State Elementary School 11 Rasau Jaya. The method used in this research is desrptive method. The form of research used in this study is Classroom Action Research (CAR). Research procedures consist of planning, implementing, observing, and reflecting. The research subject are teacher and 27 students of grade III. The research was conducted in Pematang 7 village, Rasau Jaya District, Kubu Raya Regency. The results of research he teacher’s ability to plan learning in cycle I was 2,81 an increase in cycle II became 3,35 and increased in cycle III to 3,86. The teacher’s ability to carry out learning in the cyle I namely 3,11 increased in the sycle II to 3,35 and increased in the sycle III to 3,92. Narrative writing skills in the sycle I of 73,14 increased in the sycle II to 78,33 and increased in the sycle III to 84,44 with an increase of 11,3. Thus it can be concluded that the application of the process approach can improve the narrative writing skills of grade III students at State Elementary School 11 Rasau Jaya.Keywords : Narration, Process Approach, Writing Skills